PENGARUH SOSIALISASI PERPAJAKAN, TARIF PAJAK, SANKSI PERPAJAKAN, DAN KESADARAN PERPAJAKAN TERHADAP KEPATUHAN PELAPORAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI (Studi Empiris Pada KPP Pratama Jayapura) - Marisa Setiawati Muhamad; Meinarni Asnawi; Bill J.C Pangayow (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2019)
This study aims to analyze the influence of taxation socialization, tax rates, tax sanctions, and tax awareness on tax reporting compliance Annual taxpayer person. Study at KPP Pratama Jayapura. Data collection in this study is to use questionnaires to individual taxpayers in KPP Pratama Jayapura. The sampling technique used in this research is convenience sampling. Data analysis techniques using Partial Least Square (PLS) using Smart PLS 3.0 software. Based on the results ofanalysis by using PLS test tool shows that there is influence between taxation on taxation awareness. There is an influence between taxation socialization, tax rate and tax awareness on tax reporting compliance annual taxpayer personal person. While the tax sanction does not affect the taxpayer annual reporting of the individual taxpayers. Tax awareness may interfere with the socialization of annual taxpayer's annual reporting compliance